Comparison of quality of life and psychological distress in patients with tongue cancer undergoing a total/subtotal glossectomy or extended hemiglossectomy and free flap transfer: a prospective evaluation. Issue 6 (June 2023) - Suzuki, K.; Nishio, N.; Kimura, H.; Tokura, T.; Kishi, S.; Ozaki, N.; Fujimoto, Y.; Sone, M.
Abstract: The aim of this study was to assess changes in the quality of life and psychological distress of patients with tongue cancer undergoing total/subtotal glossectomy (TG) or extended hemiglossectomy (HG) and free flap transfer. Differences between the two groups were compared using the Short Form 8-Item Health Survey (SF-8) and Hospital Anxiety and Depression Scale (HADS). Of the 43 patients with tongue cancer, 24 (56%) underwent TG and 19 (44%) underwent HG. The general health and social functioning scores in the SF-8 and depression in the HADS were significantly worse in the TG group than in the HG group at 12 months after surgery, indicating that patients in the TG group may experience social isolation and psychological distress, and have difficulty in employability even 12 months after surgery. In contrast, all items of the SF-8 in the HG group were nearly equal to those in the general population. Due to the extensive psychological impact on patients with tongue cancer who are planned for an extended resection, curative surgery with free flap transfer and multidisciplinary psychiatric support are essential to improve quality of life and manage psychological distress.